United States. Army. 1st Infantry Regiment orderly book - United States. Army. Infantry Regiment, 1st (1796-1815)
Orderly book of the regiment stationed in the Northwest Territory. Locations include Bellefontaine, Ohio, Kaskaskia, Ill., and Newport, Ky. Entries include daily orders, courts-martial, duty rosters, promotions, food and clothing provisions, and troop deployments.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army -- Order-books.; Fortification -- Illinois; Fortification -- Kentucky; Fortification -- Ohio; Military bases -- Illinois -- Kaskaskia; Military bases -- Kentucky -- Newport; Military bases -- Ohio -- Bellefontaine; Northwest, Old -- History -- 1775-1865.